Do investors and analysts value strategic corporate social responsibility disclosures? Evidence from China. (2nd January 2021) - Lu, Yingjun; Abeysekera, Indra
Abstract: This paper examines whether strategic corporate social responsibility (CSR) disclosures are value relevant for investors and analysts in the context of China. Using a sample of Chinese listed firms from One Belt One Road (OBOR) theme indices, we construct a rating system of strategic CSR disclosures including five dimensions and 20 indicators and perform a principal component analysis and a non‐hierarchical cluster analysis to group sample firms. We find that the market has a positive reaction to strategic CSR disclosures, but the market fails to perceive whether such disclosures are credible. We also find that the number of analysts following a firm is positively associated with its strategic CSR disclosures, and the positive association between strategic CSR disclosures and analysts following is less pronounced for firms with lower credibility. Additional analyses demonstrate that the higher the strategic CSR disclosure quality the more the positive market reaction and that the higher the strategic CSR disclosure quality the more the numbers of analysts following, but this positive association between disclosure quality and analysts following is discounted by a firm's lower credibility. Additional analyses further confirm that the CSR disclosure mandate has a negative moderating effect on investors' and analysts' positive reactions to strategic CSR disclosures. We do not find convincing evidence that the ownership of foreign institutional investors (QFII) has a moderating effect on investors' and analysts' reactions to strategic CSR disclosures. Finally, our extended analyses reveal that strategic CSR disclosures have a positive effect on firm performance with a complementary mediation of innovation.